Epidemiology of Traumatic Brain Injury at a Tertiary Institution in Nigeria - Omotayo Abimbola Ojo; Jennifer Chukwuamaka Okei; OyinOluwa Gloria Adaramola; Shakiru Olabisi Olajide; Opeyemi Mercy Awofeso; Chukwuemeka Abraham Agbarakwe; Bruno Jeneru Arekhandia; Bukola Samuel Owolabi; Abidat Adedamola Ashimi; Zaynab Oyindamola Solahudeen (Nigerian Postgraduate Medical Journal)
Introduction: Traumatic brain injury (TBI) is devastating to the victims, and an understanding of its prevalence, the demography and the causes help reduce the incidence and outcome. Adequate knowledge of such helps in developing preventive and management protocols in the region. The study aims to document the presentation and challenges of TBI in our centre. Methods: A cross-sectional design was conducted at Lagos University Teaching Hospital, Nigeria. Only adult (≥18 years) patients were recruited consecutively from the emergency room following a diagnosis of TBI. Data were obtained with the aid of a study pro forma which recorded participants’ sociodemographic information, pre-hospital indices and clinical examination/investigations. Imaging findings, surgical information and follow-up findings were also recorded. Data obtained were analysed using the IBM SPSS Statistics. Results: A total of 125 TBI patients with male:female of 8:1 were recruited over 12 months. The mean age was 40.8 years standard deviation ± 16.86. Only 9 patients (7.2%) had health insurance. Eighty-four (67.2%) patients had TBI from road traffic accidents (RTAs). Fall from heights, assaults, industrial accidents and gunshots contributed 16%, 9.6%, 5.6% and 1.6% of patients’ injuries respectively. One hundred and fourteen (91.2%) were brought to the hospital by non-healthcare workers. Conclusion: RTAs remain the most common cause of TBI. Majority of the populace cannot afford the cost of TBI management. The scope of national health insurance needs to be broadened to help victims at the points of need.